Metatranscriptome sequencing identifies Escherichia are major contributors to pathogenic functions and biofilm formation in diabetes related foot osteomyelitis - Radzieta, Michael; Malone, Matthew; Ahmad, Mehtab; Dickson, Hugh G.; Schwarzer, Saskia; Jensen, Slade O.; Lavery, Lawrence A. (Frontiers in Microbiology, 2022)
Osteomyelitis in the feet of persons with diabetes is clinically challenging and is associated with high rates of amputation. In this study RNA-sequencing was employed to explore microbial metatranscriptomes with a view to understand the relative activity and functions of the pathogen/s responsible for DFO. We obtained 25 intraoperative bone specimens from persons with confirmed DFO, observing that Escherichia spp. (7%), Streptomyces spp. (7%), Staphylococcus spp. (6%), Klebsiella spp. (5%) and Proteus spp. (5%) are the most active taxa on average. Data was then subset to examine functions associated with pathogenesis (virulence and toxins), biofilm formation and antimicrobial/multi-drug resistance. Analysis revealed Escherichia spp. are the most active taxa relative to pathogenic functions with K06218 (mRNA interferase relE), K03699 (membrane damaging toxin tlyC) and K03980 (putative peptidoglycan lipid II flippase murJ), K01114 (membrane damaging toxin plc) and K19168 (toxin cptA) being the most prevalent pathogenic associated transcripts. The most abundant transcripts associated with biofilm pathways included components of the biofilm EPS matrix including glycogen synthesis, cellulose synthesis, colonic acid synthesis and flagella synthesis. We further observed enrichment of a key enzyme involved in the biosynthesis of L-rhamnose (K01710 -dTDP-glucose 4,6-dehydratase rfbB, rmlB, rffG) which was present in all but four patients with DFO.